GeV-Scale Electron Acceleration in a Magnetized Plasma-Filled Waveguide by Twisted Electromagnetic Waves - Bahram Barzegar; Ali Hasanbeigi; Hassan Mehdian; Kamal Hajisharifi (Journal of Sciences, Islamic Republic of Iran)
In this paper, a test particle model is developed to study the electron acceleration in a magnetized plasma-filled waveguide by a twisted electromagnetic wave with variable amplitude and phase along the longitudinal position. With appropriately assigned initial values, the electron total energy gain is obtained using numerical analysis without calculating the dispersion relation. Numerical results show that as long as the twisted electromagnetic waves significantly affect the electron acceleration, during the passage of an electron through the waveguide, one may employ an optimum value of the external magnetic field to obtain the maximum energy gain.